Adjoint-based numerical method using standard engineering software for the optimal placement of chlorine sensors in drinking water networks. (June 2017) - Waeytens, Julien; Mahfoudhi, Imed; Chabchoub, Mohamed-Amine; Chatellier, Patrice
Abstract: To obtain representative water quality simulations, unknown model parameters have to be updated by combining information from the water quality model and the sensor outputs. An adjoint-based numerical method has been developed to determine the optimal placement of chlorine sensors in drinking water networks at a low computational cost. From a practical engineering perspective, the proposed optimal placement corresponds to the set of sensors that minimizes the area in which the unknown model parameters cannot be identified. The numerical strategy is implemented in the hydraulic software EPANET. Using the adjoint framework, we develop and apply an adaptive strategy in a French drinking water network that provides the optimal placement from 1 sensor to 6 sensors. We show that the highest reduction of the non-identifiable area is obtained at the first stages of the adaptive strategy. After 4 sensors, a plateau is reached. Highlights: Reliable water quality simulations can be reached by updating the reaction coefficient. The adjoint state allows to localize the non-coverage area for a given set of sensors. An adaptive strategy is applied to optimally place 1 to 6 sensors in a French network. The adaptive strategy is implemented in EPANET software. First stages of the adaptive strategy give the highest decrease of the non-coverage area.